The effects of the bologna process in vocational education and training: A theorized literature-based argument - Vucaj, Indrit (Journal of Interdisciplinary Studies in Education, 2015)
Bologna Process (BP), founded to meet growing challenge of international education and fulfill employment market demands in Europe (Caddick, 2008), has transformed European higher education system (EACEA P9 Eurydice, 2012) with remarkable results (Vassiliou, 2012). The Bologna Process has also led to some controversy (Cardoso et al., 2008). Some of these controversies were expressed as concerns, ranging from lack of financial reforms to adapt technical education (Reichert & Tauch, 2003) to lack of consultancy resources for technical advice (Altbach, Reisberg, & Rumbley, 2009), about BP’s impact on vocational education and training across Europe. Through theoretical framework and literature research methodology, this paper attempts to illuminate theoretically the impact that BP has had on career and technical education in Europe.